Comparison of Chest Compression Quality between Transfer Sheet and Stretcher Use for Transporting out-of-Hospital Cardiac Arrest Patients in a High-Rise Building - A Randomized and Open-Label Cross-over Design. (20th April 2021) - Chi, Chien-Yu; Renhao, Desmond Mao; Yang, Chih-Wei; Yang, Mei-Fen; Lee, Huan-Ju; Lee, Chih-Hsien; Shih, Frank Fuh-Yuan; Ong, Eng Hock Marcus; Ko, Patrick Chow-In
Abstract: Objectives: Stretchers are commonly used for transporting cardiac arrest patients, but their use may be limited in confined spaces, like elevators. Use of transfer sheet as an alternative has not been explored. We aimed to compare manual chest compression quality between these two methods. Methods: In this prospective, open-label, randomized cross-over manikin study, the subjects included emergency medical technicians who were assigned to 12 three-person crews. Scenarios included transport of a cardiac arrest in a high-rise building and elevator using transfer sheet (TS) and stretchers adjusted to 45° (S45) and 90° (S90). Chest compression quality was measured using a recording manikin and that before (on-scene phase) and after (transport phase) the manikin moved via transfer sheet or stretcher were compared. Results: The final analysis included 72 simulation runs. Chest compression quality did not differ among the groups in the on-scene phase. In the transport phase, the transfer sheet group provided greater mean compression depth (54.4 ± 4.2 vs 39.6 ± 7.2 mm, p < 0.01 and 54.4 ± 4.2 vs 40.6 ± 8.3 mm, p < 0.01, respectively) than stretchers of S45 and S90, and higher percentage of deep-enough compression (TS: 51.0 [23.8-74.8]% vs S45: 19.5 [5.8-29.5]%, p < 0.01) than the S45 group. Transfer sheet use showed a trend of lower percentages of full recoil (TS: 40.0 [12.8-64.5]% vs S45: 70.5 [47.0-79.8]% vs S90: 52.5 [25.3-76.0]%, p = 0.09). Chest compression fraction, compressions with correct hand position, and mean compression rates did not differ between groups in the transport phase. The TS group showed shorter time intervals of simulation start-to-first-compression (TS: 13.9 [12.4-15.1] sec vs S90: 15.9 [13.3-16.4] sec, p = 0.04) and total run time (TS: 145.7 [135.1-151.4] sec vs S90: 160.0 [151.9-175.4] sec, p < 0.01) than the S90 group. Conclusion: In this simulation, using transfer sheet outperform using stretcher for transporting cardiac arrest patients from high-rise buildings. Rescuers need to be aware of full chest recoil.